Heat Transfer and Fluids Properties of Nanofluids - Murshed, S M Sohel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint features a dozen high-quality research studies and reviews on different types of nanofluids and their important topics related to thermophysical and electrical properties, as well as convective and boiling heat transfer characteristics, contributed by renowned researchers around the world. It is expected to be a useful resource for related industrial professionals and researchers in this emerging and popular field of nanofluids.